Borys Hrinchenko in the memories of contemporaries - Mariia Ivashchenko (Вісник Харківського національного університету імені В. Н. Каразіна. Серія Філологія. Vìsnik Harkìvsʹkogo nacìonalʹnogo unìversitetu ìmenì V.N. Karazìna. Serìâ Fìlologìâ.)
The article analyzes the reception of B. Hrinchenko's work in criticism, elaborates studies of his contemporaries, devoted to his biography, social and literary activities. The main attention is focused on the aspect of the artist's writing work, the prerequisites for its formation, as well as the author's inherent character traits and features of appearance, which testified to the writer's strong-willed qualities and contributed to his searches. He reacted acutely to the injustice and injustice inflicted on the Ukrainian people, in particular by the numerous bans on the Ukrainian language, and was concerned with national and social issues at a time when inequality and the poor were chaining the impoverished people into chains of obedience and submission. The writer saw not the only salvation in enlightenment, the instrument of which became the embodiment of literature.